Comparison of the Foundations of Educational Sociology and Key Thinkers’ Ideas - Nurul Mawaddah Al-Mursal; Risky Aryska Putri RY; Januar (Jurnal Bina Ilmu Cendekia, 2025)
This study aims to conduct an integrated review of the basic concepts of sociology of education and the thoughts of key figures in sociology (Durkheim, Comte, Weber, Marx, Simmel) as a theoretical basis for understanding the function of education in contemporary society. The method used is a descriptive-analytical literature study with data collection from two main papers that are combined with supporting literature; the analysis is conducted through content analysis techniques to examine themes, similarities, and theoretical implications. The results of the study show that the basic concepts of educational sociology include the relationship between education and social institutions (family, economy, politics), social interactions in schools (teacher-student, student-student), the curriculum as a social construct including the hidden curriculum, and the dual role of education as an agent of reproduction and an agent of social change. The thoughts of these figures enrich the framework: Durkheim emphasizes integrative functions and norm formation, Marx highlights the reproduction of class inequality, Weber emphasizes social action and the bureaucratization of education, Comte provides a positivist methodological foundation, and Simmel highlights the dynamics of micro-interactions. In conclusion, the integration of basic concepts and the ideas of key figures produce a comprehensive theoretical framework for analyzing education policy, curriculum, and practice. The limitation of this research is that it is only based on literature, so the recommendation includes empirical field studies to test the relevance of the findings in the context of Indonesian educational practice.